2017
DOI: 10.1007/s11128-016-1501-y
|View full text |Cite
|
Sign up to set email alerts
|

Schmidt number of bipartite and multipartite states under local projections

Abstract: The Schmidt number is a fundamental parameter characterizing the properties of quantum states, and the local projections are a fundamental operation in quantum physics. We investigate the relation between the Schmidt numbers of bipartite states and their projected states. We show that there exist bipartite positive-partial-transpose (PPT) entangled states of any given Schmidt number. We further construct the notion of joint Schmidt number for multipartite states, and its relation with the Schmidt number of bip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Theorem A.2 (Block structure from Schmidt number [42]). For d 1 ≤ d 2 consider a matrix X ∈ (M d 1 ⊗ M d 2 ) + written as…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theorem A.2 (Block structure from Schmidt number [42]). For d 1 ≤ d 2 consider a matrix X ∈ (M d 1 ⊗ M d 2 ) + written as…”
Section: Discussionmentioning
confidence: 99%
“…To make our article selfcontained, we will review here some results introduced in [42] and [22] to upper bound the Schmidt number of bipartite quantum states. These results are based on a technique (called Choi decomposition) from [21] allowing to decompose a k-positive map for k ≥ 2 into the sum of a completely positive map and a (k − 1)-positive map with reduced input dimension.…”
Section: Appendix A: Schmidt Number Bounds From Block Structurementioning
confidence: 99%
“…In this section we will answer the following question, recently raised in the literature [18,Conjecture 36]: Are there PPT states ρ with an arbitrarily large difference SN(ρ)− SN(ρ Γ )? With the following theorem we demonstrate that this difference can be arbitrarily large as the local dimension grows.…”
Section: B Large Variation Of Schmidt Number Under Partial Transposimentioning
confidence: 99%
“…This gives rise to a natural question: Can high-dimensional entanglement occur at all in systems that are noisy enough to be PPT? By letting the local dimensions grow, examples of PPT states with increasingly high Schmidt number have been constructed in [18]. However, their Schmidt number scales only logarithmically in the local dimension.…”
Section: Introductionmentioning
confidence: 99%
“…Refs. [12,[21][22][23][24][25]), however the question whether PPT states can be genuinely highdimensionally entangled have been investigated only recently [26][27][28]. In particular, Huber et al [28] found that for a special class of (d × d)-dimensional PPT entangled states the Schmidt number scales as d/4.…”
Section: Introductionmentioning
confidence: 99%